2016
DOI: 10.1007/s00404-016-4138-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute-phase proteins in prediction of preeclampsia in patients with abnormal midtrimester uterine Doppler velocimetry

Abstract: Inflammation is a late event during development of preeclampsia, and acute-phase proteins are not predictive for the disease in a high-risk population without clinical symptoms during the second trimester. Progranulin is a putative new biomarker for an early detection of intrauterine growth restriction in women without concomitant hypertensive disorders. Soluble endoglin improved predictive values for preeclampsia in patients with abnormal uterine Doppler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Previous studies revealed that progranulin concentrations in the plasma are significantly higher in patients with inflammation-related disease (such as inflammatory bowel disease, rheumatoid arthritis, and systemic lupus erythematosus), as well as in infants with earlyonset sepsis compared with those without these conditions [57,58]. In the obstetric field, previous studies on maternal plasma and placental samples showed a significantly upregulated expression of progranulin in patients with preeclampsia or fetal growth restriction as compared with those without these complications [59,60]. These results contrast with the present findings on decreased plasma progranulin levels with respect to CNMM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that progranulin concentrations in the plasma are significantly higher in patients with inflammation-related disease (such as inflammatory bowel disease, rheumatoid arthritis, and systemic lupus erythematosus), as well as in infants with earlyonset sepsis compared with those without these conditions [57,58]. In the obstetric field, previous studies on maternal plasma and placental samples showed a significantly upregulated expression of progranulin in patients with preeclampsia or fetal growth restriction as compared with those without these complications [59,60]. These results contrast with the present findings on decreased plasma progranulin levels with respect to CNMM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is one of the focuses of preeclampsia research to study the molecular mechanism of trophoblast cell migration and limited invasion ability. A full understanding of the molecular changes in this process is expected to provide theoretical basis and experimental support for the prevention and treatment of preeclampsia (20). Cell scratch test is an effective method to detect cell movement.…”
Section: Comparison Of Clinical Data Between Preeclampsia Patients An...mentioning
confidence: 99%
“…Multiple recent studies have demonstrated increased serum levels of IL-1β, 171,172 IL-6, 172175 IL-8, 176 IL-10, 172,173 CRP, 172,175,177 TNF-α 172,173,175 and IFN-γ 174,178 in women with preeclampsia compared with women with normotensive pregnancies; however, these results remain inconclusive. 179 From all of the inflammatory biomarkers investigated, CRP, IL-6, IL-8, and TNF-α hold the most promise for early identification of women with preeclampsia, 180 yet there is not enough evidence supporting the prognostic ability of individual inflammatory markers in predicting the development of preeclampsia, 172,179181 which may be due to discrepancies among gestational timepoints and population studied. The combination of several biomarkers may afford greater predictive ability for identifying preeclampsia onset or prognosis, but more research is needed.…”
Section: Preeclampsiamentioning
confidence: 99%